The Use of Storyboard in Improving Narrative of Writing Text at Eight Grade Students of MTS an Nasuriyah - Kamila, Arifatul; Wahyudi , Mohammad Arief (Global Action and Education for Society, 2025)
Creating students' account composing abilities is fundamental in educating their capacity to precise thoughts coherently and inventively. This consider examines the utilize of storyboards as an guidelines instrument to progress the story composing abilities of eighth-grade students at MTS An Nasuriyah. Employing a subjective inquire about approach, information was collected through classroom perceptions, understudy composing tests, and interviews with both understudies and instructors. The discoveries demonstrate that actualizing storyboards altogether progresses students' capacity to structure their stories, create locks in storylines, and utilize suitable dialect highlights. Understudies illustrated expanded inspiration and certainty in composing after locks in with storyboard-based exercises. Besides, instructors detailed that storyboards made a difference understudies visualize their stories superior, making the composing prepare more organized and agreeable. In conclusion, the utilize of storyboards demonstrates to be an compelling methodology for making strides story composing abilities by cultivating inventiveness and organization. This consider proposes that consolidating visual helps like storyboards in composing instruction can advantage understudies in creating their narrating capacities.